Li-Fraumeni syndrome in a young patient with colorectal carcinoma (International Seven Journal of Health Research, 2024)
Li-Fraumeni syndrome is characterized as a mutation of the TP53 gene, belonging to a strain of tumor suppressor genes. Patients with mutations in this gene accumulate, throughout their lives, a greatly increased probability for the development of various types of malignant tumors. This report has as its main objective to report a clinical case of a young patient affected by a colon neoplasm, whose laboratory and anatomopathological tests indicated microsatellite instabilities. A survey was conducted in medical records of the care, exams and surgeries to which the patient was submitted for important data collection. The information obtained was compared as present in. Scientific and medical literature, and it was possible to conclude, although there is no specific genetic test that detects the TP53 gene mutation in this patient, that it presents significant changes in DNA segments, compatible with Li-Fraumeni syndrome.